Determinants of maternity waiting home utilization among women who gave birth in public health facilities in the Gedeo Zone, southern Ethiopia: an unmatched case-control study - Dawit Tilahun; Mohammed Feyisso Shaka; Moges Mareg Belay (Frontiers Media S.A., 2023)
BackgroundMaternal mortality remains unacceptably high in Ethiopia, although most of its causes are preventable. One way of tackling this problem is by establishing a maternal waiting home (MWH) close to a health facility. Although the benefits of an MWH have been well-documented, the determinants of its use have not been well-studied. This study aims to identify the determinants of utilization of an MWH among women who gave birth in public health facilities in the Gedeo Zone, southern Ethiopia.MethodsA facility-based unmatched case-control study was conducted between January 2020 and February 2020) among 129 patients belonging to the case group and 257 belonging to the control group. The data were entered into the Epi-Data version 3.1 and exported to the SPSS version 20 statistical package for analysis. Descriptive statistics such as frequency, means, and standard deviations were computed. The association between variables was checked using logistic regression analysis, and odds ratios (ORs) with 95% confidence interval (CI) were used to determine the strength of this association. A p-value of < 0.05 was used as a cutoff point to measure statistical significance.ResultA total of 378 respondents (126 cases and 252 controls) were included in the study, successfully achieving a response rate of 97.9%. The mean age of the participants was 27.4 (±5.6 SD) years, which was 28.4 (±5.5 SD) years for case group patients and 26.9 (±5.69 SD) years for control group patients. The educational status of women [adjusted odds ratio (AOR): 8.49, 95% CI: 2.91-24.7], travel time (AOR: 2.92, 95% CI:1.41-4.67), antenatal care visits (AOR: 3.54, 95% CI: 1.33-9.38), those having more than two children under the age of 5 years (AOR: 0.12, 95% CI: 0.06-0.26), those with a history of complications in previous childbirths (AOR: 4.52 95% CI: 2.41-8.47), previous place of delivery (AOR: 6.30, 95% CI: 2.71-14.78), and a lack of awareness (AOR: 5.8, 95% CI: 2.23-15.2) were all significantly associated with the utilization of an MWH.ConclusionEducational status, antenatal care follow-up, number of children under 5 years old in the household, previous place of delivery, lack of awareness regarding maternal waiting home service, and travel time were all determinants of MWH use. This implies that interventions focusing on promoting antenatal care visits, institutional delivery, and raising awareness of the benefits of MWHs are important for improving their rate of utilization.